Archaeological, industrial and biological dimensions of subterranean horror in L.T.C. Rolt's The Mine - Moshenska, Gabriel (Time and mind, 2024)
Subterranean settings are common in horror: the buried realms of darkness, demons and the dead have long and rich cultural histories. In this paper I explore three distinct themes in underground horror: the archaeological, where ancient buried mysteries meet modern interference; the industrial, where the arrogance of extractive modernity must be humbled; and the biological, where new forms of life - pale, blind, predatory - evolve in isolated darkness. To illustrate these themes I examine the 1948 short horror story The Mine by industrial historian L.T.C. Rolt, and consider how these three dimensions of the subterranean uncanny are weaved together into a striking and original tale. These are just three amongst many other cultural, literary and folkloric forms in underground horror, and this paper is intended as a starting point for further exploration of these intertwined themes.